Pengaruh Indeks Pembangunan Manusia (IPM), Tingkat Kemiskinan Terhadap Ketimpangan Pendapatan di Kota/Kabupaten Eks-Karesidenan Kedu Tahun 2020-2024 - Ningrum, Bia Satwika; Destiningsih, Rian (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2026)
The Phenomenon of income inequality in the cities/districts of the former Kedu Residency remains an important issue, as evidenced by the increase in the Gini ratio in several areas such as Magelang city and Temanggung District during the 2020-2024 period, despite the continued increase in the Human Development Index (HDI). This study aims to analyze the effect of the Human Development Index (HDI) and poverty rate on income inequality in the cities/districts of the former Kedu Residency during the period 2020-2024. The method used is panel data regression with the Common Effect Model (CEM) approach and overcoming the problem of heteroscedasticity using Robust Least Squares. The results show that the HDI has a positive and significant effect on income inequality. Meanwhile, the poverty rate has negative and significant effect at a significance level of 0.10 on income inequality. These findings indicate that improvements in human development have not been accompanied by income equality in the cities/districts of the former Kedu Residency. Therefore, poverty reduction efforts should focus on programs that can increase community income, such as economic empowerment, improving job skills, access to capital, and strengthening MSMEs. The government also needs to ensure that improvements in access to education, health services, and living standards are able to reach the lower-middle class.